2009
DOI: 10.1093/bja/aen355
|View full text |Cite
|
Sign up to set email alerts
|

Rapid pressure compensation by automated cuff pressure controllers worsens sealing in tracheal tubes

Abstract: Automated cuff pressure controllers with rapid pressure correction interfere with the self-sealing mechanism of high sealing HVLP tube cuffs and reduce their improved sealing characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 21 publications
1
32
0
2
Order By: Relevance
“…In critically ill patients, contaminated secretions can leak through the tracheal cuff and result in ventilator-associated pneumonia (2,3). High cuff pressure increases the risk for tracheomalacia and tracheal dilation in patients intubated for a long time (4). Cuff manometers are manual or automatic devices that measure the pressure in the endotracheal tube (ETT) or laryngeal mask airway (LMA) cuffs, and some can work to keep pressure at a certain level for a long time.…”
mentioning
confidence: 99%
“…In critically ill patients, contaminated secretions can leak through the tracheal cuff and result in ventilator-associated pneumonia (2,3). High cuff pressure increases the risk for tracheomalacia and tracheal dilation in patients intubated for a long time (4). Cuff manometers are manual or automatic devices that measure the pressure in the endotracheal tube (ETT) or laryngeal mask airway (LMA) cuffs, and some can work to keep pressure at a certain level for a long time.…”
mentioning
confidence: 99%
“…8,11,12 This may be favored by the time constant of the system's response that limits overcompensation (deflation) from occurring when tracheal pressure increases rapidly. 13 Moreover, by design, pneumatic systems limit overcompensation (cuff deflation) in the case of high pressure because regulation is based on a transfer of gas into the system rather than allowing cuff deflation and thus imposing iterative inflation procedures.…”
Section: Tracheal Cuff Management As Part Of a Lung-protective Strategymentioning
confidence: 99%
“…In a bench study, Weiss et al 13 suggested that cuff pressure should ideally follow airway peak inspiratory pressure to ensure sealing around the tracheal tube cuff during Dr Richard has disclosed relationships with Air Liquide Medical Systems, Covidien, Vygon, Dräger, and GE Healthcare. Dr Mercat has disclosed relationships with Covidien, Maquet, and GE Healthcare.…”
Section: Tracheal Cuff Management As Part Of a Lung-protective Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Various tubes, cuffs and pilot balloons have been designed to limit this, with very limited or short-lived efficacy. These include the Portex Profile Soft-seal TM (PSSC; Sims Portex, Kent, UK) [20], Trachelon TM gas barrier (Terumo Co. Ltd., Tokyo, Japan) [21] [17,[26][27][28][29][30][31][32][33][34][35][36][37]. Whilst these devices should, theoretically, help to ensure correct cuff pressure, none have gained widespread adoption into routine clinical practice.…”
mentioning
confidence: 99%